Medicine and Public Health in Latin America: A History - McCrea, Heather L. (My University, 2017)
Over the past three to four decades historical works focused on health and medicine in Latin America and the Caribbean have burgeoned into a rich body of scholarship. Scholars delve into a myriad of subjects using medicine and health as lenses through which structural, material, and human experiences with inequality can be analyzed across race, ethnic, gender, and economic lines. To date, much of the historical inquiry on medicine and public health in Latin America and the Caribbean has concentrated on uncovering the powerful relationships forged between medical elites, scientists, statesmen, and laypersons. In this vein, the history of Latin America and the Caribbean is situated within an interconnected globe where germs know no boundaries and disease vectors shape and reshape military campaigns and occupations, hygiene and sanitation trends, and household customs. Within this world, historical narratives and actors assume a more complex and nuanced form through scholarship that probes into the dark recesses of human suffering and the valiant (and sometimes not so altruistic) efforts of medical professionals and statesmen to launch public health campaigns to curb disease and contain contagion. Pioneering works by David Nobel Cook (1998), Alfred W. Crosby (1972), Elinor G. K. Melville (1997), and Nancy Leys Stepan (1996) laid the methodological groundwork for understanding the mechanisms that created human differences. Others have sought to tell a story about war, revolution, and social upheaval by focusing on a particular disease epidemic or public health campaign.
Citation: McCrea, H. L. (2016). Medicine and Public Health in Latin America: A History. Isis, 107(3), 614-616. doi:10.1086/688465
Keywords: History & Philosophy Of Science